Can determination of extractable organofluorine (EOF) be standardized? First interlaboratory comparisons of EOF and fluorine mass balance in sludge and water matrices. Issue 10 (21st September 2021) - Kärrman, Anna; Yeung, Leo W. Y.; Spaan, Kyra M.; Lange, Frank Thomas; Nguyen, Minh Anh; Plassmann, Merle; de Wit, Cynthia A.; Scheurer, Marco; Awad, Raed; Benskin, Jonathan P.
Abstract : The first step towards the urgently needed standardization of EOF methods for PFAS-total assessment is presented in this interlaboratory study. Abstract : The high proportion of unidentified extractable organofluorine (EOF) observed globally in humans and the environment indicates widespread occurrence of unknown per- and polyfluoroalkyl substances (PFAS). However, efforts to standardize or assess the reproducibility of EOF methods are currently lacking. Here we present the first EOF interlaboratory comparison in water and sludge. Three participants (four organizations) analyzed unfortified and PFAS-fortified ultrapure water, two unfortified groundwater samples, unfortified wastewater treatment plant effluent and sludge, and an unfortified groundwater extract. Participants adopted common sample handling strategies and target lists for EOF mass balance but used in-house combustion ion-chromatography (CIC) and liquid chromatography-tandem mass spectrometry (LC-MS/MS) methods. EOF accuracy ranged from 85–101% and 76–109% for the 60 and 334 ng L −1 fluorine (F) – fortified water samples, respectively, with between-laboratory variation of 9–19%, and within-laboratory variation of 3–27%. In unfortified sludge and aqueous samples, between-laboratory variation ranged from 21–37%. The contribution from sum concentrations of 16 individual PFAS (∑PFAS-16) to EOF ranged from 2.2–60% but extended analysis showed that other targets were prevalent, in particular ultra-short-chain perfluoroalkyl acids ( e.g. trifluoroacetic acid) in aqueous samples and perfluoroalkyl acid-precursors ( e.g. polyfluoroalkyl phosphate diesters) in sludge. The EOF-CIC method demonstrated promising accuracy, robustness and reporting limits but poor extraction efficiency was observed for some targets ( e.g. trifluoroacetic acid).